Optimal improvement of direct power control strategy based on sliding mode controllers. (October 2018) - Lhachimi, Hicham; Sayouti, Yassine; El Kouari, Youssef
Highlights: The DPC-SVM combined with SMC are more faster and robust compared to the conventional DPC-SVM with PI controllers. The proposed SMC are simple and ensure more resistance during voltage unbalance. The proposed SMC behaves as a second order and thus the chattering phenomenon is reduced. Abstract: In electricity generation, the power quality reflects the waveform, harmonic contents and service availability. In a connection with an electrical network, the power transmitted to the grid must attain its optimal value. Therefore, an effective regulation is essential for improving the produced energy to address disturbances that can affect the system. In this study, direct power control (DPC) strategy based on sliding mode controllers (SMC) is implemented to enhance the robustness of the doubly fed induction generator (DFIG). The proposed nonlinear technique combined with the space vector modulation (SVM) algorithm strengthens the system to render it immune to parameter variation and yields a reasonable quality of the waveform of the stator current under weak grid faults. In addition, the power ripples are reduced, and a reasonable total harmonic distortion (THD) rate is ensured by using a three level inverter. The application of such sliding mode controllers achieves smooth power regulation and increases the dynamic response of the system. The simulation is carried out on a 1.5-MW DFIG-based wind energy conversion system (WECS). The performances achieved by the proposed control strategy are investigated under several conditions.